2018
DOI: 10.1177/0748730418757006
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Complete Excision of Conditional Alleles in the Mouse Suprachiasmatic Nucleus by Vgat-ires-Cre

Abstract: Mice with targeted gene disruption have provided important information about the molecular mechanisms of circadian clock function. A full understanding of the roles of circadian-relevant genes requires manipulation of their expression in a tissue-specific manner, ideally including manipulation with high efficiency within the suprachiasmatic nuclei (SCN). To date, conditional manipulation of genes within the SCN has been difficult. In a previously developed mouse line, Cre recombinase was inserted into the vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Discordant Mice Have a Slow but Robust Central Circadian Clock. The GABAergic nature of SCN neurons (44) allowed the use of the Vgat-Cre + driver to target conditional alleles of CK1δ and CK1« (12) in the SCN and other GABAergic brain areas (45,46), although not directly affecting circadian clocks in peripheral tissues. Deletion of different combinations of CK1δ/« alleles in GABAergic neurons significantly lengthened the circadian period of both behavioral (F 5,150 = 356.5, P < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Discordant Mice Have a Slow but Robust Central Circadian Clock. The GABAergic nature of SCN neurons (44) allowed the use of the Vgat-Cre + driver to target conditional alleles of CK1δ and CK1« (12) in the SCN and other GABAergic brain areas (45,46), although not directly affecting circadian clocks in peripheral tissues. Deletion of different combinations of CK1δ/« alleles in GABAergic neurons significantly lengthened the circadian period of both behavioral (F 5,150 = 356.5, P < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of the role of food timing in the regulation of torpor might thus be confounded by the presence of circadian regulation. To study the isolated role of food timing in controlling the timing of torpor, we next disrupted endogenous circadian rhythmicity by disrupting the essential clock gene Bmal1 in GABAergic neurons including the SCN, while leaving clocks in peripheral tissues effectively wildtype (Vgat-Cre + Bmal1 fl/fl ; Weaver et al, 2018). Food was provided at 24 h (2.2 g) or 20 h (1.8 g) intervals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Six female wild-type C57BL/6J mice were purchased from Jackson Laboratories. Vgat-Cre + CK1δ fl/fl ε fl/+ mice (5 male, 4 female) (van der Vinne et al, 2018), Vgat-Cre + Bmal1 fl/fl mice (5 male, 5 female) and No-Cre Bmal1 fl/fl mice (5 male, 7 female) (Weaver et al, 2018) were generated by crossing previously described genotypes (Etchegaray et al, 2009;Storch et al, 2007;Vong et al, 2011). Genotyping was performed using ear or tail biopsies by PCR as described previously (Etchegaray et al, 2009;Weaver et al, 2018).…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…Indeed, the SCN is necessary to drive behavioral and feeding rhythms. Early studies of SCN lesions (29) and recent SCN-enriched selective knockouts of clock genes (30,31) confirmed that without a functional central clock, animals in constant darkness are arrhythmic in their FIGURE 1 | The mammalian molecular clock. The complex of BMAL1 and CLOCK rhythmically binds E-box elements to activate the transcription of clock-controlled genes (CCG), including other parts of the core clock which form the negative arm of the feedback loop.…”
Section: Synchronization Of Peripheral Clocks By the Scnmentioning
confidence: 99%